Prevalence of Fall among Elderly in Rural Sabah and Its Associated Factors - Khalid Mokti; Mohd. Yusof Ibrahim; Syed Sharizman Abd Rahim; Mohammad Saffree Jeffree; Mazlinda Musa; Mohd. Rohaizat Hassan; Yugo Shobugawa; Muhammad Aklil Abd Rahim; Ahmad Faizal Roslan; Mervynn Koon Kar-Wai (Jurnal Keperawatan Indonesia, 2026)
Falls are a leading cause of injury among older adults, often resulting in significant physical, psychological, and social consequences. This study aims to determine the factors that contribute significantly to fall risks among the older adults in rural Sabah. A cross-sectional community study was conducted in the Kudat Division, Sabah, Malaysia from January to June 2021. Using multistage random sampling, 700 adults aged ≥60 years were recruited, excluding those with severe disability, mental illness, or institutionalized. Data were collected through face-to-face interviews with a structured questionnaire adapted from the validated Japanese Gerontological Evaluation Study (JAGES) tool, and anthropometric measures were taken to calculate body mass index (BMI). Logistic regression was performed in SPSS version 27 to identify factors associated with falls. The prevalence of falls among the elderly is 19%. The significant factors include the age ≥80 years old: higher adjusted odds ratio (AOR) for falls (AOR = 2.01); overweight: significantly higher risk (AOR = 4.17); walking difficulty: elevated risk (AOR = 1.69); and poor current health status: increased likelihood of falls (AOR = 1.88). In conclusion, these findings highlight key demographic and health-related factors associated with falls among the rural elderly population, contributing to a clearer understanding of fall risk in non-urban settings.